2011
DOI: 10.4155/bio.11.93
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Developing a Bioanalytical Method for a Macrolide Immunosuppressant Compound by LC–MS/MS

Abstract: The quantification of tacrolimus in human whole blood was developed by LC-MS/MS for a range of 50.0 to 50,000.0 pg/ml. Different challenges were faced during method development due to ion-suppression, lack of sensitivity and low recovery. The optimization of the extraction procedure played a crucial role as tacrolimus had to be isolated from red blood cells, to which it is strongly bound. Another particular challenge arose from the freeze-thaw stability where the extracted samples from fresh blood always showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In HPlc-MS/MS method development for a macrolide immunosuppressant, matrix effects prevented successful validation and introduction of HrMS/ MS considerably reduced chemical noise [20]. A first example of a full validation of a bioanalytical method using HrMS was published by Fung et al [46] for the quantification of prednisone and prednisolone in human plasma.…”
Section: High Resolution Ms For Peptide Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…In HPlc-MS/MS method development for a macrolide immunosuppressant, matrix effects prevented successful validation and introduction of HrMS/ MS considerably reduced chemical noise [20]. A first example of a full validation of a bioanalytical method using HrMS was published by Fung et al [46] for the quantification of prednisone and prednisolone in human plasma.…”
Section: High Resolution Ms For Peptide Quantificationmentioning
confidence: 99%
“…However, the product ion spectrum is scanned at high resolution instead of unit resolution. For small molecules, it has been reported that selection of product ions at high resolution can improve selectivity and specificity [20]. However, the challenges of the scan time paradigm discussed for SrM workflows are also relevant for HrMS SrM.…”
Section: Does Hrms Srm Offer a Valuable Strategy?mentioning
confidence: 99%
See 1 more Smart Citation
“…3 And other LC-MS/MS methods commonly used zinc sulfate (ZnSO 4 ) and methanol or acetonitrile as protein precipitant. [20][21][22] Zinc sulfate is a nonvolatile inorganic salt which is di cult to remove after entering the mass spectrum. The instrument is easy to get dirty, which increases the frequency of maintenance and cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy and precision data shows that intra-and interassay bias and coefficient of variation (CV) were <20% for LLOQ and <15% for quality control samples ( 123 . The addition of a washout step with isopropyl alcohol: tetrahydrofuran (90:10) in between runs has helped minimize build-up of ion-suppressing matrix components which seemed to have a more pronounced effect at lower analyte concentrations.…”
Section: Accuracy and Precisionmentioning
confidence: 99%